PELAKSANAAN PROGRAM TRANSISI KE PASCA-SEKOLAH BAGI TUNAGRAHITA RINGAN DI SLBN CENTER PAYAKUMBUH - Devi Syari Nanda (Universitas Negeri Padang, 2014)
Abstrak: This research was conducted due to the existence of transition program to post-school for the students with mild mental retardation at SLBN Center Payakumbuh. This was started from the phenomena indicating that the school was qualified to provide the program of independence. The purpose of this research was to observe the implementation of transition program to post-school for the students with mild mental retardation at SLBN Center Payakumbuh. This was a descriptive research which used qualitative approach. The data was collected through observation, interview and documentation study. The result of the research relevated that: (1) The role of educators in the implementation of the transition programs to post-school such; the principal was responsible for the activities and did evaluation; the teachers had a role as the guide to help students raise the quails, the students with mild mentar retardation were trained everyday to manage quail farms by using continuous training method, the training system used referred to the real workplace and in its implementation the students got salary, (2) the cooperation patterns were started from enticing the partners by making use of the people engaged in the marketing of quail eggs which was then managed proffesionally, (3) the cooperation between SLBN Center an the companies was not in the from of written agreement but just used an oral agreement that has been approved by both parties. The school then was expected to develop the quail farm program into a potential business for the students with mild mental retardation in the future. Keywords: Transition program, mild mental retardation, quail farm, cooperation with companies.